Cardiovascular-related conditions and risk factors in primary care for deprived communities before and during the COVID-19 pandemic: an observational study in Northern England. Issue 11 (22nd November 2022) - Fu, Yu; Price, Christopher; Haining, Shona; Gaffney, Bob; Julien, David; Whitty, Paula; Newton, Julia L
Abstract : Objectives: The North East of England, ranked as having the highest poverty levels and the lowest health outcomes, has the highest cardiovascular disease (CVD) premature mortality. This study aimed to compare CVD-related conditions and risk factors for deprived practice populations with other general practice (GP) populations in Northern England to England overall, before and during COVID-19 to identify changes in recorded CVD-related risk factors and conditions and evidence-based lipid prescribing behaviour. Design: A population-based observational study of aggregated practice-level data obtained from publicly accessible data sets. Setting: 34 practices that fall into the 15% most deprived practice populations in England were identified as the most deprived communities in the North East and North Cumbria (Deep End). Participants: Patients aged ≥16 registered with GP and diagnosed with any form of CVD. Primary and secondary outcome measures: CVD-related conditions and risk factors, statin prescribing. Results: Deep End (n=263 830) had a smaller, younger and more deprived population with lower levels of employment and full-time education and higher smoking prevalence. They had some higher recorded CVD-related conditions than England but lower than the non-Deep End. Atrial fibrillation (−0.9, –0.5), hypertension (−3.7, –1.3) and stroke and transient ischaemic attack rates (−0.5, –0.1) appeared to be lower in the Deep End than in the non-Deep End but the optimal statin prescribing rate was higher (3.1, 8.2) than in England. Conclusion: Recorded CVD-related risk factors and conditions remained comparable before and during COVID-19. These are higher in the Deep End than in England and similar or lower than the non-Deep End, with a higher optimal statin prescribing rate. However, it was not possible to control for age and sex. More work is needed to estimate the consequences of the pandemic on disadvantaged communities and to compare whether the findings are replicated in other areas of deprivation.